2007
DOI: 10.1590/s0102-05362007000100009
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biomassa e óleo essencial de hortelã em hidroponia em função de nitrogênio e fósforo

Abstract: A tualmente, o cultivo de plantas medicinais assume importância mundial devido à demanda exercida pelas indústrias químicas, farmacêuticas, alimentícias e de cosméticos. Essa importância justifica o forte investimento em pesquisas com plantas medicinais, principalmente, na busca por novas ferramentas de investigação, determinação e síntese de produtos naturais (Di Stasi, 1996). Entretanto, tem-se estudado muito pouco os mecanismos relacionados à produção, sob os aspectos quantitativos e qualitativos, dessas su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
6
0
4
Order By: Relevance
“…However, in studies with Mentha piperita L. an increase in roots production with the lower P dose in the nu- trient solution was not observed [18]. It should be noted that the P dose at which the plants produced more shoot mass corresponds to only half of the higher P dose (2 mmol•L −1 ) used in this research nutrient solution and in other solutions used in hydroponics for most crops [7] [19]- [21].…”
Section: Biomass Productionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, in studies with Mentha piperita L. an increase in roots production with the lower P dose in the nu- trient solution was not observed [18]. It should be noted that the P dose at which the plants produced more shoot mass corresponds to only half of the higher P dose (2 mmol•L −1 ) used in this research nutrient solution and in other solutions used in hydroponics for most crops [7] [19]- [21].…”
Section: Biomass Productionmentioning
confidence: 82%
“…In a previous study with plants of Mentha piperita was also observed that stem is the preferential organ for storage of this nutrient [7]. The nitrate accumulation in stem may be a plant evolutionary strategy to prevent the excess of nitrate in the leaves and to maintain the N supply for biochemical activities in low availability periods [15] [24] [25].…”
Section: Nitrogen Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…As espécies de menta já foram definidas por diversos autores, como muito exigentes quanto a nutrição mineral em cultivos em solo e em hidroponia (Ram & Kumar, 1997;Rodrigues et al, 2004;Valmorbida & Boaro, 2007;Souza et al, 2007;Garlet et al, 2007). Dentre as CHAGAS JH; PINTO JEBP; BERTOLUCCI SKV; SANTOS FM; BOTREL PP; PINTO LBB.…”
unclassified
“…Os fatores que afetaram a produção de biomassa seca da parte aérea afetaram também o teor e rendimento de extrato de A. chica, como observado por diversos autores que encontraram maiores rendimentos de óleos essenciais com o aumento dos níveis de nutrientes proporcionados pela adubação orgânica (Ferreira et al, 2004;Souza et al, 2007;Sales et al, 2009;Chagas et al, 2011).…”
Section: Teor E Rendimento De Extratosunclassified